2012
DOI: 10.1186/1475-2875-11-63
|View full text |Cite
|
Sign up to set email alerts
|

Modelling malaria treatment practices in Bangladesh using spatial statistics

Abstract: BackgroundMalaria treatment-seeking practices vary worldwide and Bangladesh is no exception. Individuals from 88 villages in Rajasthali were asked about their treatment-seeking practices. A portion of these households preferred malaria treatment from the National Control Programme, but still a large number of households continued to use drug vendors and approximately one fourth of the individuals surveyed relied exclusively on non-control programme treatments. The risks of low-control programme usage include i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(42 citation statements)
references
References 37 publications
0
42
0
Order By: Relevance
“…Largely, these concept has been applied mostly to diarrhoea, cholera and malaria [43][44][45], and [46][47][48]. Although these studies have shown great potential in identifying the covariates for this disease, no study has been found in the literature that applied the same analytical tool to the study of length of stay of typhoid patients in Ghana.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Largely, these concept has been applied mostly to diarrhoea, cholera and malaria [43][44][45], and [46][47][48]. Although these studies have shown great potential in identifying the covariates for this disease, no study has been found in the literature that applied the same analytical tool to the study of length of stay of typhoid patients in Ghana.…”
Section: Discussionmentioning
confidence: 98%
“…The conditional variance of the Negative Binomial distribution exceeds the conditional mean. A general class of Negative Binomial is given in [42], and [43]. The variance function is…”
Section: Mean Of the Negative Binomial Distributionmentioning
confidence: 99%
“…Regularly updated malaria risk maps (Haque et al, 2010b;Reid et al, 2010Reid et al, , 2012Haque et al, 2011;Wang et al, 2014) can help the NMCC to monitor progress and mobilize resources. Distance, population density, treatment seeking behavior and other health facilities should be considered (Ahmed et al, 2009;Haque et al, 2012;Simon et al, 2013). Accessibility (road network) proved to be a significant risk factor in this study for clinical diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…A properly specified OLS regression can predict the variability in the dependent variable [47] since it meets all of the following requirements: (i) coefficients for model explanatory variables, which are statistically significant and have the expected sign; (ii) explanatory variables free of multicollinearity; (iii) model not biased (heteroscedasticity); (iv) residuals normally distributed; (v) no missing key explanatory variables; (vi) residuals free of spatial autocorrelation; and (vii) enough adjusted R-Squared to explain the variability of the dependent variable [48][49][50][51]. The exploratory regression tool (ArcGIS 10.1 (Esri, Redlands, CA, USA) helped us to find a good OLS model by attempting every possible combination for a set of explanatory variables; we selected the one that met all of the requirements of the OLS method and, notably, had a high-adjusted R 2 [52].…”
Section: Ols Regression Requirementsmentioning
confidence: 99%